A POLICY PRINCIPLE: POLLUTED PAYS PRINCIPLE - Annapurna Pattnaik , Rubi Talukdar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
When someone knowingly spoils another person’s water, not just allow him to cause harm, he or she may purify the water, or cistern. Polluter Country Theory has now become a popular term in recent times. That is the key basis of this slogan, if you make a mistake, clean it up. Realize that the polluter pays hardly a concept in environmental law means ’fault.’ It likes a sample size to reclaim coral reef damage. The polluting party pays for harm done to just the natural ecosystem under environmental legislation. The tradition is considered significant due to its economic strength in most OECD and European Community (EC) countries. This article discusses the context and application of this theory at the national level as well as the major gaps in India implementation process. In conclusion, the author discusses the big problem facing the country in its implementation.